A novel composite scaffold of Cu-doped nano calcium-deficient hydroxyapatite/multi-(amino acid) copolymer for bone tissue regeneration - Mou P (Dove Medical Press, 2019)
Ping Mou,1 Haitao Peng,2 Li Zhou,3 Lin Li,2 Hong Li,2 Qiang Huang11Department of Orthopedic Surgery, West China Hospital, West China Medical School, Sichuan University; 2School of Physical Science and Technology, Sichuan University; 3Core Facility of West China Hospital, Sichuan University, Chengdu, Sichuan Province 610041, People’s Republic of ChinaBackground and methods: A Cu-doped composite scaffold of nano calcium-deficient hydroxyapatite (n-CDHA)/multi(amino acid) copolymer (MAC) was prepared. The structure, porosity, morphology and compressive strength of the scaffolds were characterized, the in vitro degradability in phosphate-buffered solution (PBS) and cell responses to the scaffolds were investigated, and in vivo stimulation of bone formation were analyzed.Results: The scaffolds showed the compressive strength of approximately 12 MPa and total porosity of about 81%. Weight loss of the composite scaffolds was 63% after 16-week immersion in PBS. Cu release in scaffolds showed a marked dependence on the initial amount in the scaffolds over time. Cu-doped n-CDHA/MAC scaffolds with the content of Cu 0.5% and 1% in mass ratio showed better cell responses to proliferation and differentiation of rat bone marrow stromal cells (rBMSCs) than that with no Cu. After 12-week implantation in rabbits, 1% Cu-doped n-CDHA/MAC showed better ability of angiogenesis and osteogenesis compared to 0% Cu-doped n-CDHA/MAC.Conclusion: The 1% Cu-doped n-CDHA/MAC composite scaffold showed good capacity of angiogenesis and osteogenesis, and the Cu showed positive effects on cell growth and osteogenesis. And it has potential to be used as bone regeneration scaffolds.Keywords: calcium-deficient hydroxyapatite, multi-(amino acid) copolymer, copper, osteogenesis, degradability, cytocompatibility